Reducing livestock abortions and calf mortality to improve food security and lower GHG emissions in Tanzania and Kenya - Slater, Annabel; Arndt, Claudia; Balcha, Endale (International Livestock Research Institute, 2024)
The global livestock sector emits 12% of all GHG emissions associated with human activities, with cattle meat and milk alone contributing 62% of these emissions. Meat demand will triple and milk demand double in Africa by 2050 due to population growth, increased incomes and urbanization. When this happens, higher livestock production will directly increase emissions of enteric methane, a potent greenhouse gas (GHG). However, this can be mitigated through measures that make the livestock sector more efficient by lowering mortality during pregnancy and mortality of calves. Currently, approximately 20% of global livestock production is lost annually through disease, of which a significant amount is through abortions and calf mortality. An East African study by ILRI’s Mazingira Centre and Centre For Tropical Livestock Genetics and Health (CTLGH) researchers, together with international partners, finds that livestock abortions (stillbirths) and calf mortality in Tanzania and Kenya cause a loss of animal protein equivalent to the per capita consumption of approximately 5.2 million people. The study shows that preventing abortions in cattle could lower milk GHG emission intensity (EI)—the amount of GHG produced per unit of meat—by 4.6%, while in goats, the reduction could reach as high as 15.8%. Halving calf mortality would reduce EI by 3%, and eliminating calf mortality would therefore reduce by 6%.